ANALISIS FATWA DSN-MUI NO.28/DSN-MUI/III/2002 TENTANG JUAL BELI MATA UANG - Okto Viandra Arnes (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
Buying and selling a common contract used by the community. One of the current buying and selling is and selling currency. Currency transactions can be carried out by one body/company or individuallly with various purposes. Every time yuo make a currency sale and purchase transaction, the exchange rate is used. This exchange rate can fluctuate according to conditions from time to time caused by various factors such as economic and political factors. Money has a big role in various economic streams, because money is a barter tool, a measure of value and a means of paying debts and cash. Buying and selling currency or alsharf is a from economic activity that is influential in fulfilling the basic needs of modern human ilfe today, buying and selling currency may be carried out both in buying and selling similar currencies or currincies of different types as long as it is paid in cash and the exchange rate done must be of equal value. This exchange rate must be in accordance with the principles of islamic law in order to avoid usury, gharar and maysir. Based on the backround above, the formulation of the problem in this study is how ti analyse the legal basis of the DSN No.28/DSN-MUI/III/2002 concerning buying and selling currency (Al-Sharf). This research was conducted by means of a qualitative approach. Then this type of research is library (library research), which is a way of collecting data through the library, examining the literature in the books that exist in relation to the title. The data processing technique is through the inductive method and the analytical method. The results obtained from this study are that the system in the operational mechanism for buying and selling currencies must be based on the Al-Qur’an, Hadis and Ijma. Currency buying and selling is a transaction that is permisible in Islam in accordance with certain laws that have been explain by syara’.